“Nato nella medesima terra irrigua”. Gabriele D’Annunzio, the Last Heir of Ovid - Gagliastro, Donato (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
Throughout Gabriele d’Annunzio’s vast and multiform productions, Ovid’s presence shines through with the strength of a model both ancient and modern. Since his years at the “Cicognini”, he feels bound to Ovid by a similarity “in lyrical ways” and by a relationship of “consanguinity” based on their common origins. The assiduity in Ovid’s readings, testified to by the large number of volumes of the Augustan poet in the library of the Vittoriale, is reflected in a dense network of echoes – some perspicuous, others subtle – that can be found in the Vate’s most famous works. During his twilight years, d’Annunzio’s nocturnal exploration finds singular affinities with the Ovidian elegies of exile to which he feels attracted the most. Even in the nascent silent film industry, d’Annunzio, creator and forerunner of fashions, sees a prodigious form of visual art that has in Ovid a millenary antecedent. Beyond the unavoidable differences separating the two temporally distant authors, the paper attempts to outline an overall profile of the correspondences and possible equations between d’Annunzio and Ovid without pretense of exhaustiveness. In the wake of perspectives inaugurated by distinguished masters, it is an attempt to offer cues for interpreting, from the vestiges of classicism, d’Annunzio’s art within the Ovidian framework.